THE ROLE OF FERMENTED FOODS IN REGULATING GUT MICROBIOTA AND MENTAL HEALTH: A Literature Review - Kadek Ardhyani Widya Ningrum; Aristanto Prambudi (Journal of Diverse Medical Research : Medicosphere, 2025)
Background: Scientifically, fermentation is the process by which microorganisms convert sugar into alcohol and organic acids, which extends the shelf life of food. Today, the field of Nutritional Psychiatry has emerged to identify food components that are important for mental health, emphasizing that the complex interaction between nutrition and brain function highlights the need for a multidisciplinary approach. Objective: To explore the role of fermentation-based diets in regulating gut microbiota and their impact on mental health. Methods: The research method used was a literature review, with five journals reviewed. Results: Based on the five research journals reviewed, the main findings centered on the crucial and comprehensive relationship between gut microbiota, nutrition (diet), and mental health. The first journal introduced psychobiotics, specific live microorganisms that provide therapeutic benefits for mental disorders by increasing the production of important neurotransmitters such as dopamine and serotonin in the gut. The second and fourth journals explicitly show a strong correlation between a healthy diet and mental well-being. The third journal specifically discusses the role of fermented foods in Nutritional Psychiatry. The fifth journal also discusses lifestyle and nutritional neuroscience related to mental health. Conclusion: There is a close relationship between gut microbiota, diet, and mental health, which indicates the potential of nutritional and psychobiotic interventions in the prevention and treatment of mental disord